Revolutionizing Indonesian Language Learning: The Effectiveness of Kurikulum Merdeka at SMP Negeri 2 Selong - Al-Pansori, Muh. Jaelani; Mohzana, Mohzana; Pransisca, Made Ayu (IJE : Interdisciplinary Journal of Education, 2025)
The Independent Curriculum was officially introduced by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in February 2022. Its implementation requires several preparatory steps, including curriculum planning, differentiated instruction, and assessment strategies. This study aims to examine and describe the planning, implementation, and evaluation of the Independent Curriculum in the Indonesian language subject at SMPN 2 Selong. A qualitative descriptive research approach was employed, utilizing data collection techniques such as observations, interviews, and document analysis. The data were analyzed through qualitative methods, including data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the Independent Curriculum in Indonesian language instruction at SMPN 2 Selong has been conducted effectively and sustainably. However, several challenges remain, such as limited teaching resources, inadequate infrastructure and internet access, difficulties in adapting to students’ diverse linguistic backgrounds and dialects, time constraints in project-based learning, insufficient exposure to differentiated learning models, and the persistence of traditional assessment paradigms that do not fully align with the principles of the Independent Curriculum.